In vivo imaging of membrane type‐1 matrix metalloproteinase with a novel activatable near‐infrared fluorescence probe. Issue 8 (31st July 2014) - Shimizu, Yoichi; Temma, Takashi; Hara, Isao; Makino, Akira; Kondo, Naoya; Ozeki, Ei‐ichi; Ono, Masahiro; Saji, Hideo
<x xml:space="preserve">Abstract</x> Membrane type‐1 matrix metalloproteinase (MT1‐MMP) is a protease activating MMP‐2 that mediates cleavage of extracellular matrix components and plays pivotal roles in tumor migration, invasion and metastasis. Because in vivo noninvasive imaging of MT1‐MMP would be useful for tumor diagnosis, we developed a novel near‐infrared (NIR) fluorescence probe that can be activated following interaction with MT1‐MMP in vivo. MT1‐hIC7L is an activatable fluorescence probe comprised of anti‐MT1‐MMP monoclonal antibodies conjugated to self‐assembling polymer micelles that encapsulate NIR dyes (IC7‐1, λem: 858 nm) at concentrations sufficient to cause fluorescence self‐quenching. In aqueous buffer, MT1‐hIC7L fluorescence was suppressed to background levels and increased approximately 35.5‐fold in the presence of detergent. Cellular uptake experiments revealed that in MT1‐MMP positive C6 glioma cells, MT1‐hIC7L showed significantly higher fluorescence that increased with time as compared to hIC7L, a negative control probe lacking the anti‐MT1‐MMP monoclonal antibody. In MT1‐MMP negative MCF‐7 breast adenocarcinoma cells, both MT1‐hIC7L and hIC7L showed no obvious fluorescence. In addition, the fluorescence intensity of C6 cells treated with MT1‐hIC7L was suppressed by pre‐treatment with an MT1‐MMP endocytosis inhibitor (P < 0.05). In vivo optical imaging using probes intravenously administered to tumor‐bearing mice showed that MT1‐hIC7L specifically visualized C6 tumors (tumor‐to‐background ratios: 3.8 ± 0.3 [MT1‐hIC7L] vs 3.1 ± 0.2 [hIC7L] 48 h after administration, P < 0.05), while the probes showed similarly low fluorescence in MCF‐7 tumors. Together, these results show that MT1‐hIC7L would be a potential activatable NIR probe for specifically detecting MT1‐MMP‐expressing tumors.